Return to Education Estimation on Self-Employment Entrepreneurs and Their Comparison with Workers in Indonesia - Dwi Wahyudi; Muhammad Hanri (Politeknik Statistika STIS, 2021)
Entrepreneurship in various pieces of literature is mentioned as one aspect that adds value to a country's economy. Using Sakernas August 2019 data and the Mincer income model, this study estimates the educational investment in self-employed entrepreneurs. The results show a positive effect between years of schooling and income earned. Compared to workers, the level of assessment of entrepreneur education looks lower. In addition, this study also looks at how income among entrepreneurs. The Gini coefficient shows 0.47 for self-employed entrepreneurs and 0.41 for workers. There is a sizeable amount of income inequality for self-employed entrepreneurs.